Blood Transfusion Practices in Intensive Care: A Prospective Observational Binational Study - Flint, Andrew W. J.; Poole, Alexis; Raasveld, Senta Jorinde; Bailey, Michael; Brady, Karina; Chen, Pin-Yen; Chen, Yan; Cooper, D. Jamie; French, Craig; Higgins, Alisa; Irving, Adam H.; McAllister, Richard E.; et al. (Critical care explorations, 2025)
IMPORTANCE: Blood transfusions are a common and potentially lifesaving intervention in ICU patients but are associated with harm and often transfused inconsistently with guidelines. However, it is not well known how ICU transfusion practice has recently changed and if there is variation in transfusion practice. OBJECTIVES: To describe blood transfusion practices in ICU, the variation in practice across sites, and to compare transfusion practices against national guidelines and with prior published practice. DESIGN, SETTING, AND PARTICIPANTS: A prospective, multicenter, binational, observational study conducted in 40 Australian and New Zealand ICUs from October 2021 to July 2022. All adult (≥ 18 yr) ICU patients admitted over 1 week were included and followed until ICU discharge or 28 days. MAIN OUTCOMES AND MEASURES: Types of transfusion, thresholds and reasons for transfusions, the use of viscoelastic hemostatic assays (VHAs), variation in transfusion practice across sites, and changes in transfusion practice over time. RESULTS: Of 927 patients, 217 (23.4%) received a blood transfusion during their ICU admission-192 (20.7%) received RBCs, 63 (6.8%) received platelets, 49 (5.3%) received fresh frozen plasma (FFP), and 29 (3.1%) received cryoprecipitate. Massive transfusion protocols were implemented nine times for six patients (0.7%). VHA were used in 25 of 268 (9.3%) non-RBC transfusions. Compared with national guidelines, 89.0% of RBC transfusions, 30.3% of platelet, 27.4% of FFP, and 20.0% of cryoprecipitate transfusions were consistent. Compared with ICU transfusion practices in 2008, after adjusting for confounding variables, ICU patients who received RBC and FFP were transfused more units each, and variation in total transfusions across sites increased for RBC, platelets, and FFP. CONCLUSIONS AND RELEVANCE: Blood transfusions are common in ICU, but the practice is heterogeneous and frequently inconsistent with national guidelines, and the number of units transfused per patient has increased. More evidence is required.